Cover Image. (29th June 2020) - Wang, Yu; Zhang, Jiaqi; Feng, Wei; Cao, Haiyan; He, Qiaoyue; Xu, Jinzhi; Zeng, He; Xie, Mingxing
Abstract : The back cover image is based on the Original Article Description of misdiagnosis and missed diagnosis of fetal complex heart malformations by prenatal echocardiography combined with postnatal cardiovascular casting by Yu Wang et al., https://doi.org/10.1002/pd.5689 . Abstract : The back cover image is based on the Original Article Description of misdiagnosis and missed diagnosis of fetal complex heart malformations by prenatal echocardiography combined with postnatal cardiovascular casting by Yu Wang et al., https://doi.org/10.1002/pd.5689 .